Demonic divine : Himalayan art and beyond - Linrothe, Robert N., 1951-; Busta, Carly; Rhie, Marylin M., 1937-2020; Watt, Jeff, 1957- (New York : Rubin Museum of Art ; Chicago : Serindia Publications, 2004)
Maak kennis met de kunst uit de Himalaya waarbij vooral aandacht besteed wordt aan de goede en kwade Goden die door de plaatselijke inwoners aanbeden worden.
Includes index.
Item is published in conjunction with the exhibition "Demonic divine : Himalayan art and beyond" held at the Rubin Museum of Art, New York, October 2, 2004-January 9, 2005.
Keywords: Art, Tibetan -- Himalaya Mountains Region -- Exhibitions; Buddhist art -- Himalaya Mountains Region -- Exhibitions; Buddhist gods -- Himalaya Mountains Region -- Exhibitions